Knowledge of the Madurese Community-Indonesia Regarding Bioprospection of the Traditional Herb Kamandin Saebo (Glossocardia leschenaultii [Cass.] Veldkamp) (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2023)
The purpose of this study was to describe the knowledge of the Sumenep Madura community (village elders and gatherers) about the Kamandin Saebo (Glossocardia leschenaultii) plant and its utilization. This study uses observational research that aims to observe a fact at a certain time using a descriptional approach model. The research was conducted in the Sumenep-Madura area, East Java Province. The research was conducted in July 2023-August 2023 by observational method. We discussed the results of information regarding the knowledge of the Sumenep people about the existence and growing areas of Kamandin saebo, a literature search regarding the morphological characterization, benefits, or uses of Kamandin saebo in medicine as conveyed by the gatherers. We also found that Kamandin Saebo is of great value. There are 14 healing functions associated with Kamandin Saebo. The Madurese people believe this plant to have many benefits or even cure all diseases.